Sorção de cádmio e chumbo em solo ácido tratado com biocarvão de eucalipto - Silveira, Gabriel José Lima da (2022)
The Pollution of soil and water by heavy metals grows more and more with the disorderly increase of human activities; therefore, management strategies to control these pollutants must be developed in parallel. The possibility of heavy metals being retained in biochar particles, due to the interaction mechanisms of this material with metals, makes the use of this input very relevant, since it is a promising alternative. In this research, the potential of biochar produced from eucalyptus wood under slow pyrolysis (400 to 450 °C) in cadmium (Cd) and lead (Pb) sorption was investigated using the laboratory batch method. The investigation was carried out through three experiments: in the first, the soil was incubated with biochar to form the substrate, which was later used in the sorption tests, in which the second experiment used Cd and Pb at concentrations of 10 mg L-1 and 150 mg L-1, respectively, in a monoelementary system to determine the removal capacity and the percentage of sorption. In the third experiment, sorption isotherm tests were used at concentrations of 0, 5, 10, 15, 20, 25 and 30 mg L-1 for Cd and 0, 25, 50, 75, 100, 125 and 150 mg L-1 for Pb, only for the treatment that obtained the highest percentage of removal of Cd and Pb in the second experiment. Soil incubation with biochar was carried out in a dark room and sorption experiments were carried out at the Soil Chemistry Laboratory, both sites belonging to the Soil Science Department of the Federal University of Ceará, Fortaleza, Ceará. The experimental design for the first two experiments was completely randomized (DIA), in a 3x4 factorial scheme, with four replications, combining different particle sizes <0.5; 0.5-1 and 1-2 mm and different doses of biochar 0%, 1%, 3% and 5% v/v incubated in acidic soil (pH 4.5). The treatment that obtained the highest percentage of removal of both metals was the one with particle size <0.5 mm at the dose of 5% biochar. The results of the isotherms showed that the soil treated with biochar with particle size <0.5 mm at the 5% dose had a maximum sorption capacity of 891.9 mg kg-1 for Cd and 3281.8 mg kg-1 for Pb. The sorption process was well described by the isothermal equations of Langmuir and Freundlich.